2015
DOI: 10.1186/s40200-015-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the Apolipoprotein A5 gene in Moroccan patients with the metabolic syndrome

Abstract: BackgroundIn this case–control study we investigated the relative contribution of commons APOA5 polymorphisms and haplotypes to the risk of metabolic syndrome in Moroccan patients.MethodsUsing the International Diabetes Federation (IDF) criteria for metabolic syndrome, the study included 176 patients and 105 controls. We genotyped APOA5 polymorphisms (−1131 T > C, c.56C > G, c.553G > T and c.1259 T > C) by PCR-RFLP analysis. The effects of APOA5 polymorphisms and constructed haplotypes on metabolic syndrome we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 43 publications
(48 reference statements)
3
6
0
1
Order By: Relevance
“…The patients carried -1131 T > C SNP was associated with increased TG level, waist circumference, fasted glucose and reduced HDL levels. These data confirmed the association of -1131 T > C variants with the predisposition to metabolic syndrome [ 50 ].…”
Section: Apoa5 Gene Polymorphisms On Obesity and The Metabolic Syndrosupporting
confidence: 84%
“…The patients carried -1131 T > C SNP was associated with increased TG level, waist circumference, fasted glucose and reduced HDL levels. These data confirmed the association of -1131 T > C variants with the predisposition to metabolic syndrome [ 50 ].…”
Section: Apoa5 Gene Polymorphisms On Obesity and The Metabolic Syndrosupporting
confidence: 84%
“…We found that the -1131T>C polymorphism was significantly associated with MetS. This association has been previously reported among some European, Asian, and African populations [12,[24][25][26][27][28][29][30]. The -1131C allele has also been shown as a risk factor for MetS among obese adolescents [30].…”
Section: Discussionsupporting
confidence: 85%
“…A haplotype consisting of the −1131C, c.56C, c553G, and c.1259T alleles has been shown to be associated with the MetS in Morracan patients [29]. Additionally, a haplotype which contains the minor alleles of -1131T>C, IVS3+476G>A, and c.1259T>C was shown to be higher in patients with hypertriglyceridemia than the control subjects [34].…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study, we reported the association of APOA5 variants (rs651821 and rs3135506) with MetS and its traits [19]. Other studies reported the involvement of rs662799 (−1131T>C) in MetS [15,20,21].…”
Section: Introductionmentioning
confidence: 85%